Dampak Covid – 19 Dalam Stabilitas Ekonomi Politik Internasional - Siti Imalia Tanjung (Jayapangus Press, 2021)
The unprecedented COVID-19 pandemic has caused people all over the world to panic. The World Health Organization (WHO) is taking proactive measures to prevent the spread of the virus, by directing countries around the world to take measures such as social distancing, physical distancing, quarantine, and regional restrictions or known as lock down which ultimately affects various sectors of life. . This research journal discusses the Impact of Covid-19 on International Political Economy Stability. This paper focuses on the impacts of the COVID-19 pandemic phenomenon, and various global problems in general, and positions the COVID-19 pandemic phenomenon from the point of view of international political economy studies as a study of International Relations. This writing uses a qualitative descriptive research method by using a literature study to systematically study the impact of the COVID-19 Pandemic on the stability of the International Political Economy, in order to formulate future policies in combating the pandemic. After reviewing and analyzing some of the literature, it was concluded that the stability sector of the International Political Economy is the most vulnerable and threatened to the impact of COVID-19.